2008
DOI: 10.1590/s1806-37132008001000002
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do questionário de controle da asma validado para uso no Brasil

Abstract: Objective: To evaluate whether the Portuguese version of the Asthma Control Questionnaire (ACQ) is a valid instrument to measure asthma control in adult outpatients in Brazil. Methods: We selected 278 outpatients diagnosed with asthma. All of the patients completed the questionnaire, underwent spirometry and were clinically evaluated by a physician in order to characterize the control of the disease in the first visit. The questionnaire was evaluated in three versions, with 5, 6 and 7 questions, respectively, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
1
16

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(56 citation statements)
references
References 19 publications
0
34
1
16
Order By: Relevance
“…(22) Individuals with poor perception of asthma control might be at increased risk of severe exacerbations, given that they fail to detect worsening in time to institute preventive treatment, (23) as well as constituting a group at increased risk of developing respiratory failure. (24) In 2008, Leite et al (10) calculated the sensitivity and specificity of the ACQ-6 relative to the evaluation by a specialist. Using an ACQ-6 score of 1.5 as a cut-off point, those authors found a sensitivity of 77%, a specificity of 84%, a positive predictive value of 0.9, and a negative predictive value of 0.67 in the identification of uncontrolled asthma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(22) Individuals with poor perception of asthma control might be at increased risk of severe exacerbations, given that they fail to detect worsening in time to institute preventive treatment, (23) as well as constituting a group at increased risk of developing respiratory failure. (24) In 2008, Leite et al (10) calculated the sensitivity and specificity of the ACQ-6 relative to the evaluation by a specialist. Using an ACQ-6 score of 1.5 as a cut-off point, those authors found a sensitivity of 77%, a specificity of 84%, a positive predictive value of 0.9, and a negative predictive value of 0.67 in the identification of uncontrolled asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Scores ≥ and < 1.5, respectively, indicate uncontrolled asthma and controlled asthma. In that study, (10) there was a comparison between the ACQ scores and the evaluation of asthma control by a pulmonologist, which was used as the gold standard for classifying asthma control, including information regarding pulmonary function. It was concluded that the questionnaire was a good identifier of uncontrolled asthma, which is a major concern in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to the first experimental session, patients were submitted to the Asthma Control Questionnaire (ACQ-7), duly validated 11 to assess the effectiveness of asthma control 12 . Patients were selected to perform 2 distinct experimental sessions on 2 nonconsecutive days.…”
Section: Experimental Designmentioning
confidence: 99%
“…Diversos estudos sobre a asma têm sido publicados no Brasil e no exterior contendo normatizações de condutas, que são os guidelines [17,18,19,20,21,22,23,24]. Esses estudos visam à ampla difusão do conhecimento sobre o tema e a uma correta abordagem diagnóstica com vistas ao tratamento adequado.…”
Section: Diagnóstico De Asmaunclassified